2008
DOI: 10.1002/jez.477
|View full text |Cite
|
Sign up to set email alerts
|

The acute temperature tolerance of green sturgeon (Acipenser medirostris) and the effect of environmental salinity

Abstract: We investigated the effect of environmental salinity on the upper thermal tolerance of green sturgeon (Acipenser medirostris), a threatened species whose natural habitat is vulnerable to temperature and salinity variation as a result of global climate change. Freshwater (FW)-reared sturgeon were gradually acclimated to salinities representing FW, estuary water (EST), or San Francisco Bay water (BAY) at 18 degrees C, and their critical thermal maximum (CTMax) was measured by increasing temperature 0.3 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…The effect was small, with a 0.4°C decrease in CTmax from 34.5±0.2 to 34.1±0.1°C for 0.25 to 2.0 %BM day −1 rations, respectively. These values are similar to a previously reported CTmax value of 34.2±0.1°C for slightly smaller (58 g) green sturgeon acclimated to the same temperature (Sardella et al 2008). Though the biological significance of a 0.4°C effect of feeding ration on CTmax is debatable, small differences in CTmax can reflect biologically significant performance differences at high temperatures.…”
Section: High Temperature Tolerancesupporting
confidence: 89%
See 1 more Smart Citation
“…The effect was small, with a 0.4°C decrease in CTmax from 34.5±0.2 to 34.1±0.1°C for 0.25 to 2.0 %BM day −1 rations, respectively. These values are similar to a previously reported CTmax value of 34.2±0.1°C for slightly smaller (58 g) green sturgeon acclimated to the same temperature (Sardella et al 2008). Though the biological significance of a 0.4°C effect of feeding ration on CTmax is debatable, small differences in CTmax can reflect biologically significant performance differences at high temperatures.…”
Section: High Temperature Tolerancesupporting
confidence: 89%
“…Temperature was then increased at a rate of 0.3°C min −1 under the control of a YSI 72 Proportional Temperature Controller (YSI, Yellow Springs, OH, USA), while gill ventilation movements were monitored. The CTmax of an individual fish was determined as the temperature at which gill ventilation movements ceased, which is an end point commonly used in CTmax tests on fishes (Fangue and Bennett 2003), including green sturgeon (Beitinger and Bennett 2000;Sardella et al 2008). …”
Section: Ctmaxmentioning
confidence: 99%
“…The upper temperature tolerance of feed-restricted (12.5%, 25%, 50% OFR) and non-feed-restricted (100% OFR) green and white sturgeon juveniles were determined following standard CTMax methodology for teleost fishes (0.3°C/min; e.g., Fangue and Bennett, 2003) and used previously in sturgeon research (Sardella et al, 2008;Verhille et al, 2015). Following the four-week feed restriction trial, fish from each feed restriction group (N = 12, four fish per replicate tank for a given feed restriction group) were individually placed in one of four half-full, 57 L glass aquaria for 30 min (18.6 ± 0.5°C, mean ± SEM).…”
Section: Critical Thermal Maximum (Ctmax)mentioning
confidence: 99%
“…Further investigations are needed to examine whether the magnitude of changes in the aerobic scope would differ between the two sturgeon species at a similar stage of development with acclimation to elevated temperature, in association with feed restriction. Previous studies in green sturgeon have demonstrated that metabolic rate increases with temperature (Sardella et al, 2008) and it would be useful to better understand whether green sturgeon become oxygen limited at a lower temperature than white sturgeon when food restricted (Pörtner and Farrell, 2008). This could be particularly important for the juvenile life stage undergoing transitions from freshwater to seawater on their outward migration out of the SFBD and into the coastal ocean.…”
Section: Ctmaxmentioning
confidence: 99%
“…However, photoperiod and diel seasonal cycles are also crucial in the determination of CT max (Lutterschmidt and Hutchison, 1997), as are salinity and diet. For example, Sardella et al (Sardella et al, 2008) recently demonstrated that salinity affects the acute temperature tolerance of green sturgeon (Acipenser medirostris), and the presence of microbial levan in the diet of rohu fish (Labeo rohita) increased CT max temperatures (Gupta et al, 2010). Acute temperature tolerance may also be affected by prior exposure to aquatic contaminants.…”
Section: Thermal Tolerancementioning
confidence: 99%